Guidelines for the Application of Information Technology in Financial Institution: A case study of Ban Khlong Sai Saving Group 972, Baan Khlong Sai Nai, Yupo Subdistrict, Mueang District, Yala province - Masamae, Isamail; Petchrat, Supamach (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI: 10.14456/pnuhuso.2023.1 This research aims 1) to study the process of using technology in the community financial institution of the Ban Khlong Sai Saving Group and 2) to study the ways to develop information technology to use in the community financial institution. This is a mixed-method study which the samples included 16 financial institution committee and 100 members of community financial institution, selected by purposive sampling. The research instrument included a questionnaire and an interview form. The quantitative data were analyzed by statistics; frequency, mean, and standard deviation while the qualitative data were analyzed by content analysis. The results of this study showed that 1) the information technology was used in the community financial institution, for example, the account system. It was found that computers and its supporting devices were not enough for personnel, and some personnel were lack of knowledge and skills on computer program. They were familiar with manual system which could lead to mistakes 2) The ways to apply the information technology in work indicated three suggestions as follows: First, the numbers of computers should be arranged sufficiently for personnel. Second, the channels of communication with members of financial institution should be diverse and third, the personnel should be trained on knowledge and skills about information technology.